1999
DOI: 10.1530/eje.0.1400425
|View full text |Cite
|
Sign up to set email alerts
|

Regression of cardiac abnormalities after replacement therapy in Addison's disease

Abstract: Objective: To evaluate by echocardiography the cardiac structure and function in patients with primary adrenocortical insufficiency. Design and Methods: Two-dimensionally guided M-mode echocardiograms and spectral Doppler studies were performed in seven consecutive patients with newly diagnosed autoimmune primary adrenal failure before and 4-8 months after an adequate regimen of steroid substitution. Echocardiographic parameters were also studied in ten healthy controls. Results: In the cases with untreated Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…In addition, patients with Addison disease, a lifethreatening disorder characterized by decreased production of glucocorticoids, present with weak hearts (20). Although heart failure secondary to Addison disease has been described (21), cardiac hypertrophy has not been reported, perhaps reflecting the diagnosis and effective treatment of individuals before cardiac abnormalities become severe (22). Alternatively, because Addison disease operates at a systemic level and is also accompanied by insufficient mineralocorticoid signaling, the resulting heart pathology in these patients may differ from the cardiac abnormalities detected in the cardioGRKO mice, where glucocorticoid signaling is deficient only in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients with Addison disease, a lifethreatening disorder characterized by decreased production of glucocorticoids, present with weak hearts (20). Although heart failure secondary to Addison disease has been described (21), cardiac hypertrophy has not been reported, perhaps reflecting the diagnosis and effective treatment of individuals before cardiac abnormalities become severe (22). Alternatively, because Addison disease operates at a systemic level and is also accompanied by insufficient mineralocorticoid signaling, the resulting heart pathology in these patients may differ from the cardiac abnormalities detected in the cardioGRKO mice, where glucocorticoid signaling is deficient only in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Fallo et al . described reduced left ventricular dimensions in untreated patients with Addison's disease, which normalized after substitution 26 and Allolio et al . found impaired left diastolic relaxation after 48 h of withdrawal of glucocorticoid therapy 27 .…”
Section: Discussionmentioning
confidence: 96%
“…However, it was quite surprising to find that all included patients had concentric remodelling of the left ventricle, despite the young age of participants and the absence of hypertension or other concomitant disease. Fallo et al described reduced left ventricular dimensions in untreated patients with Addison's disease, which normalized after substitution 26 and Allolio et al found impaired left diastolic relaxation after 48 h of withdrawal of glucocorticoid therapy. 27 Aldosterone has trophic effects on the myocardium, but its role in the nonfailing heart seems modest.…”
Section: P-value* Startmentioning
confidence: 99%
“…Four patients also had echocardiographic signs of mitral valve prolapse (MVP) without evidence of mitral regurgitation. After corticosteroid replacement, LV chamber size normalized and MVP resolved . Hypovolemia did not provide an adequate explanation for these findings, as baseline blood pressure and heart rate were normal.…”
Section: Cardiac Dysfunction In Adrenal Insufficiencymentioning
confidence: 90%